Relationship between TIM-3 Immune Response Expression and Nasopharyngeal Carcinoma Histopathology - Harahap, Vina Andita; Farhat, Farhat; Nursiah, Siti; Yudhistira, Ashri; Sitompul, Ramlan; Harahap, Juliandi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Nasopharyngeal carcinoma is a malignancy of the nasopharyngeal epithelium that is often diagnosed at an advanced stage and is associated with impaired immune regulation in the tumor microenvironment. T-cell immunoglobulin and mucin domain-3 (TIM-3) is an immune checkpoint molecule that plays a role in suppressing the antitumor immune response. This study aims to analyze the relationship between TIM-3 immune response expression and the histopathological type of nasopharyngeal carcinoma. An analytical study with a cross-sectional design was conducted on 40 paraffin blocks of nasopharyngeal carcinoma patients at H. Adam Malik General Hospital, Medan, selected by consecutive sampling. TIM-3 expression was analyzed using real-time polymerase chain reaction (RT-PCR) with the calculation of ΔCT values against the control gene β-actin. Univariate analysis was used to describe the characteristics of the subjects, while bivariate analysis used the Kruskal–Wallis test to assess the relationship between TIM-3 expression and histopathological type. The majority of subjects were male (65%) with a mean age of 48.2 ± 11.1 years. The most common histopathological type was non-keratinizing squamous cell carcinoma (90%). The mean TIM-3 expression was 4.3 ± 1.6 with a median of 4.8 (−0.1–6.7), and 97.5% of samples showed increased expression. The Kruskal–Wallis test showed no significant correlation between TIM-3 expression and histopathological type (p = 0.452). It was concluded that TIM-3 expression is generally increased in nasopharyngeal carcinoma, but is not significantly associated with histopathological type. Further research is needed to evaluate the biological role and therapeutic potential of TIM-3 in this disease.